1999
DOI: 10.1111/1468-5957.00261
|View full text |Cite
|
Sign up to set email alerts
|

Survey and Market‐based Evidence of Industry‐dependence in Analysts’ Preferences Between the Dividend Yield and Price‐earnings Ratio Valuation Models

Abstract: Prior research has shown that analysts' preferred valuation models are the price-earnings (PE) ratio and the dividend yield. This paper presents strong evidence that the relative importance of these two models varies according to stock market sector. Companies in the services, industrials and consumer goods sectors are shown to be 'PE-valued' while financials and utilities companies are shown to be 'yield-valued'. These findings are derived from survey research and then tested in a market-based model. This use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 28 publications
5
44
1
3
Order By: Relevance
“…dividend payout as perfectly normal for a water company is consistent with the greater importance of dividends in valuing utility companies compared with other companies, as perceived both by analysts (Barker, 1999) and executives (Dhanani, 2005). Gearing policies have been somewhat more varied than dividend policies.…”
Section: 10supporting
confidence: 55%
“…dividend payout as perfectly normal for a water company is consistent with the greater importance of dividends in valuing utility companies compared with other companies, as perceived both by analysts (Barker, 1999) and executives (Dhanani, 2005). Gearing policies have been somewhat more varied than dividend policies.…”
Section: 10supporting
confidence: 55%
“…Book building produce elevated expected returns thus allowing the issuer to sell the securities at full value but in it the exposure to risk is higher, whereas, fixed priced offerings places issuer in guaranteed certain profits even though at lower prices. Barker (1999) [10] , Bradshaw (2002) [11] , observed that the P/E standard was used extensively for evaluating an IPO. On examination of 103 specialist information (in USA), Bradshaw found that the experts made use of P/E method and anticipated its evaluation to be an important value motivator for equity.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Professional equity investors' main aim is to maximize risk-adjusted stock returns relative to a benchmark or index and assess whether shares are over/undervalued with reference to uncertain future cash flows or earnings (Arnswald, 2001;Barker, 1999a). They therefore require information for estimating future cash flows and/or earnings and associated risk (or future returns).…”
Section: Outside Professional Equity Investorsmentioning
confidence: 99%
“…Early evidence (Pike et al, 1993;Vergoossen, 1993;Barker, 1999a) shows the Price/Earnings ratio is widely used by analysts and fund managers, with DCF models being less influential. However, more recent evidence shows DCF models are used more than earnings models, particularly in growth industries (Demirakos et al, 2004;Glaum and Friedrich, 2006).…”
Section: Use Of Valuation Modelsmentioning
confidence: 99%